Las acrobacias fáciles en el suelo y su influencia en el estado de ánimo de adolescente - León Chicaiza, Damaris Geomara (2024)
This research aims to determine the influence of effortless acrobatics on the floor (Rol-Vertical- Arch- Lateral Wheel) to improve the mood of adolescents in the gymnastics school of the Sports Federation of Chimborazo with a group of adolescents in the range of 10 to 12 years. The study argues that the practice not only improves adolescents' physical condition and skills but also positively influences their emotional well-being. This study examined various mood states using the POMS (Profile of Athletes' Mood States) questionnaire. Consequently, a decrease in anger, fatigue, tension, and depressed state was obtained. Therefore, there was an increase in the factors of vigor and friendship to understand how easily acrobatics on the floor can influence mood. It is highlighted that effortless floor acrobatics encompasses physical, cognitive, and emotional dimensions. The type of research is quasi-experimental, as it includes both qualitative and quantitative data collection through the manipulation of variables. The research aimed to address a gap in scientific knowledge about the relationship between easy floor acrobatics and adolescent mood, providing concrete answers to generate a positive impact on the lives of adolescents. The findings of this study have practical implications for the design of adolescent health and sports psychology programs. Finally, it was concluded that easy floor acrobatics significantly influence the emotional well-being of adolescents participating in the easy acrobatics program.